1996
DOI: 10.1515/jpme.1996.24.5.489
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for patients with recurrent abortion with positive antiphospholipid antibodies using a traditional Chinese herbal medicine

Abstract: Twelve patients with recurrent abortion who had shown positive antiphospholipid antibodies were treated through the administration of a Japanese modified traditional Chinese herbal medicine Sairei-To (Chan ling-Tang) The patients had experienced a total of 27 spontaneous abortions in their previous pregnancies and had no other pregnancy history except for one patient. The patients were treated with 9.0 g of Sairei-To per day before their next pregnancy. The positive value of antiphospholipid antibodies returne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…Carreras et al [3] reported that lupus anticoagulant suppressed the production of prostacyclin in the aortic endothelial cells of mice, and they suggested that this condition may induce the production of thromboxane A2, which is a strong vasoconstrictor and inducer of platelet aggregation, and that this would be followed by the formation of thrombi. We and other authors have reported the effectiveness of immune suppression and anticoagulant therapy for patients with recurrent fetal miscarriage who were positive for lupus anticoagulant or aCL-Ab [2,8,13,23,28].…”
Section: Discussionmentioning
confidence: 92%
“…Carreras et al [3] reported that lupus anticoagulant suppressed the production of prostacyclin in the aortic endothelial cells of mice, and they suggested that this condition may induce the production of thromboxane A2, which is a strong vasoconstrictor and inducer of platelet aggregation, and that this would be followed by the formation of thrombi. We and other authors have reported the effectiveness of immune suppression and anticoagulant therapy for patients with recurrent fetal miscarriage who were positive for lupus anticoagulant or aCL-Ab [2,8,13,23,28].…”
Section: Discussionmentioning
confidence: 92%
“…None of the participants showed the presence of any genetic impairment, uterine anomalies, endocrine or metabolic disorders. The mean age of the patients was 31 ± 3.8 (25-36) years the number of fetal wastage was 3.6 ± 1.85 (2)(3)(4)(5)(6)(7)(8), and the number of living children was 0.5 ± 0.66 (0-2) (table I).…”
Section: Methodsmentioning
confidence: 98%
“…The suppression of autoimmune factors by prednisolone and anticoagulant therapy by low-dose aspirin was considered to improve the pathophysiology of recurrent abortion in these patients. We adopted a Chinese herbal medicine, Saireito, for the patients rather than prednisolone on the basis of the report that Saireito enhanced the effects of glucocorticoid hormones in vivo, and reported the efficacy of the treatment [6,9]. It is well known that prednisolone has many side effects, which led us to use Saireito.…”
Section: Introductionmentioning
confidence: 99%
“…To treat the positive antiphospholipid antibodies, the Japanese traditional herbal medicine, Sairei-to (Tsumura, Tokyo, Japan; 9 g/ day), which may have a corticosteroid hormone-like pharmacological effect, 7 and low-dose aspirin (81 mg/ day) were administrated according to our previously reported protocol. [8][9][10] The titer of anticardiolipin antibody normalized after the administration of Sairei-to. The wife conceived her third pregnancy, and this pregnancy continued beyond her critical period of 10 weeks of gestation.…”
Section: Casementioning
confidence: 96%